European Sustainable Workforce Survey - Wave 2 - Van der Lippe, Tanja (Utrecht University, 2022)
A sustainable European workforce has become increasingly relevant in our present day and age. Flexibility and job insecurity are omnipresent; organizational workforces are displaying growing diversity with respect to age, gender, ethnicity and family status; and Europe’s welfare states are delegating more and more responsibility for the well-being of workers to employers. Now more so than ever, organizations need to consider investing in workers to improve their performance and level of satisfaction. These investments can take many forms, including flexible work arrangements, training plans, child-related policies and health programs. The crucial question is how to make this happen. Why do some organizations invest more and others less in their employees? Why do some employees make use of these investments and while others do not? Why do such investments sometimes improve employee performance and satisfaction and sometimes not? To do so, we collected information from employees in many organizations in various sectors across nine European countries.

This data package contains the cleaned data, codebooks and questionnaires for the second wave of the European Sustainable Workforce Survey.
Keywords: Social Sciences - Sociology (5.4); Sustainable workforce; Organisations; Employees; Managers; Organisational policies; Survey data; Multi-level data; Employee-employer linked data; European Sustainable Workforce Survey; Europe